2011
DOI: 10.1097/jom.0b013e3182135973
|View full text |Cite
|
Sign up to set email alerts
|

Coping With the Impact of Working in a Conflict Zone

Abstract: Although personnel who went to war zones or suffered trauma were more psychologically symptomatic, the increased burden of symptoms was not associated with frank illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…While some studies suggest longer deployments increased the risk of adverse psychological health effects (Ames et al, 2007;Hibberd & Greenberg, 2011;McCarroll et al, 2000), possibly as a result of increased exposure to an accumulation of highly challenging exposures, other findings on this topic have been less consistent. Thus further research on the impact of deployment length and frequency is required.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While some studies suggest longer deployments increased the risk of adverse psychological health effects (Ames et al, 2007;Hibberd & Greenberg, 2011;McCarroll et al, 2000), possibly as a result of increased exposure to an accumulation of highly challenging exposures, other findings on this topic have been less consistent. Thus further research on the impact of deployment length and frequency is required.…”
Section: Discussionmentioning
confidence: 94%
“…While many emergency responders view work overseas positively (Hibberd & Greenberg, 2011;Thoresen et al, 2009) some return with psychological problems (Shah et al, 2007). The Health and Safety Executive (2007) identified six primary workplace stressors: work demands; control over work; support; relationships; role and responsibilities and organisational change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that many aspects of humanitarian work might affect psychological well-being, [1][2][3][4][5][6] although emergency workers responding to a disaster overseas often have viewed their work positively. 6,7 In this study, we sought to understand the experiences of FCO staff in Japan after the 2011 earthquake. Our objective was to identify factors that increased or alleviated their stress.…”
mentioning
confidence: 99%
“…The review also found that longer tour lengths were associated with increased rates of alcohol problems and posttraumatic stress disorder [8], increased rates of diagnosis of mental disorders for the wives of deployed personnel [5] and increased spousal aggression on return from tour [6]. While these conclusions were mostly derived from military studies, there has also been research carried out in other organizations including those that employ international relief workers [4,9,10]. This previous review [3] revealed a number of practical conclusions, including a potential for detrimental consequences when deployment length is extended [8,11], when personnel deal with circumstances outside their control or if a diplomat's future plans are perceived as unpredictable.…”
Section: Introductionmentioning
confidence: 99%